The Brazilian Trade Liberalisation: the regionalized impacts on the productive chain of cotton, textile and apparel industries - Cassio Frederico Camargo Rolim (European Regional Science Association (ERSA), 1998)
During the last 8 years Brazil has experiencing a large program of commercial overture. A lot of administrative and tax barriers had suppressed and the textile sector had been one of the most affected by this process. The paper analyses the regional impact of this process over the so-called textile chain (cotton-textile-confections) utilising dates of production and sales from 1980 until 1994 for the most important production regions in Brazil. These informations are analyzed by nonparametrical statistics. In a synthesis, the commercial overture that happened in Brazil during the last 8 years didn't change the structural tendencies in the spatial division of work of the production links of Cotton, Textile and Confections. It incremented the Cotton March to West, the concurrence among decadent textiles regions as Pernambuco, Minas Gerais and S?o Paulo and those, more dynamics, as Santa Catarina and Ceara. The commercial overture has been a double, because are growing the exports and imports figures of Textile. On the other hand those that are still using old technologies, are closing the plants. But the price of this adjusting process was paid by the cotton's farmers and, maybe, by the small and medium firms of Confections. The new regions are growing due to different factors. Ceara, in the northwest of Brazil, due to fiscal incentives by SUDENE and advantages from direct importation of cotton from Africa. Santa Catarina, in the south, due to a special characteristic of its industrial organisation and a new territorial organisation of production buying cotton from Argentina, Paraguay and Parana (Brazil) and inputs textile from EEC.
Keywords: 330